The Social Theories of the press: journalism and society - Marocco, Beatriz (Brazilian journalism research, 2005)
For a short period of time, between the end of the 19th century and the middle of the 20th, newspapers and journalists were under the spotlight as never before. However, the comprehensive reviews of the theories of the press do not acknowledge the thought of this period and its development into “the social theories of the press” (H. Hardt, 1979). This article is positioned in this gap of press studies, and it uses as a starting point the foucaultian description of the diﬀ erent thresholds that establish the levels of discourse elaboration (Foucault, 1995). It aims at exploring the theoretical production that approximates German and American scholars such as Albert Schäffle (1831-1903); Karl Knies (1821-1898); Karl Bücher (1847-1930); Ferdinand Tönnies (1835-1936); Albion Small (1854-1926); Edward Ross (1856-1951); Max Weber (1864-1920); Robert Park (1864-1944) and Walter Lippmann (1889-1974), rescuing this production from the pre-history of the press to materialize evidence that this production coincides, in its external origin, with the modern newspaper practices, although there seemed to be no dependence between them at the time.